Hubungan riwayat pemberian asi eksklusif, asupan zat gizi makro, perilaku hidup bersih dan sehat terhadap status gizi balita usia 3 – 5 tahun di Kelurahan Kedaung - Bintang Fachri Elnady; Ibnu Malkan Bakhrul Ilmi; Avliya Quratul Marjan (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Underweight in toddlers can occur due to several factors, including inadequate intake of macronutrients, non-exclusive breastfeeding, and poor knowledge and behavior regarding clean and healthy living practices (PHBS).Objectives: To analyze the relationship between the history of exclusive breastfeeding, dietary intake, as well as knowledge and attitudes towards clean and healthy living practices (PHBS) with the nutritional status (weight-for-age/WFA) of children aged 3–5 years in Kedaung Village.Methods: This study used a cross-sectional design with a total sample of 42 respondents selected through clustered random sampling. Samples were drawn from two kindergartens in different RWs in Kedaung. Data were collected through questionnaires, SQ-FFQ interviews, and anthropometric measurements of children's nutritional status (WFA). Data analysis included univariate descriptive analysis and bivariate analysis using the chi-square test.Results: The study found a significant relationship between energy intake (p=0,013), carbohydrate intake (p=0,000), and PHBS knowledge (p=0,003) with nutritional status (WFA) among toddlers. This indicates that higher energy intake, carbohydrate intake, and PHBS knowledge are positively correlated with better nutritional status (WFA). Meanwhile, other variables such as fat intake, protein intake, clean and healthy living behaviors, and exclusive breastfeeding were not significantly associated with nutritional status (WFA) (p-value > 0,05).Conclusions: Energy intake, carbohydrate intake, and PHBS knowledge are significantly associated with the nutritional status (WFA) of toddlers.